INTEGRATING CRITICAL THINKING INTO LMS-SUPPORTED TOEIC INSTRUCTION: TRANSFORMING WASHBACK IN EFL LEARNING - Eka Uliyanti Putri; Lilis Stianingsih (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The integration of Learning Management Systems (LMS) in English language learning has become increasingly common in higher education. This study investigated the implementation of critical-thinking-oriented activities in LMS-supported TOEIC instruction and its influence on students’ TOEIC achievement, critical thinking skills, washback effects, and learning perceptions. The study employed a mixed-methods quasi-experimental design involving 60 undergraduate students enrolled in TOEIC preparation classes at a private university in Indonesia. Quantitative data were collected through TOEIC tests and a washback questionnaire, while qualitative data were obtained through semi-structured interviews. The findings showed that students in the experimental group achieved higher TOEIC score gains and demonstrated better critical thinking performance than those in the control group. The questionnaire results indicated high levels of learning orientation, deep learning behavior, learner autonomy, reflective learning, and engagement in LMS-supported activities, while negative washback tendencies were relatively low. Interview findings revealed positive student perceptions of the learning approach.